Damage imaging of concrete wall-like structures using cylindrical concrete implantable module. (May 2023) - Yang, Ziqian; Chen, Qingjun; Li, Menglei; Yuan, Cheng; Zhang, Minghui; Kong, Qingzhao
In this study, an implantable array-based sensing technique for damage imaging of concrete wall-like structures was developed. Unlike conventional concrete damage imaging methods that require several distributive transducers instrumented in the detection structure, the proposed technique integrates a multi-transducer into a cylindrical concrete implantable module (CCIM) that can be directly implanted into the wall-like structures to transmit and receive probe signals based on a sensing array. Implantable designs within integrated sensing elements benefit the management of devices and provide a new transducer-to-structure installation for structural health monitoring (SHM). Furthermore, to analyze the received probe signals and visualize the structural defects, a novel damage-imaging algorithm aimed at a heterogeneous concrete medium was proposed. The algorithm assumed that each point in the detection space was a virtual scatter to simulate a series of signal transceiving processes using a computer. The virtual scattered signals received by the CCIM were projected onto the signals received under real damage conditions to reconstruct an imaging map. The reliability of the developed technique for damage imaging of heterogeneous concrete wall-like structures was studied both numerically and experimentally. The numerical study employed a 2-D mesoscale model considering concrete as a multiphase composite material and revealed the stress-wave propagation law in concrete. In the experiment, two fabricated CCIMs were implanted into a concrete wall-like specimen for signal transmission and reception. The imaging results acquired by simulation and experiment both successfully displayed the damaged area and exhibited excellent prospects for the implantable array-based sensing technique in SHM.